1995
DOI: 10.1042/bj3070609
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid-induced Ca2+ mobilization in human A431 cells: structure-activity analysis

Abstract: Lysophosphatidic acid (LPA; 1-acyl-sn-glycero-3-phosphate) is a platelet-derived lipid mediator that activates its own G-protein-coupled receptor to trigger phospholipase C-mediated Ca2+ mobilization and other effector pathways in numerous cell types. In this study we have examined the structural features of LPA that are important for activation of the Ca(2+)-mobilizing receptor in human A431 carcinoma cells, which show an EC50 for oleoyl-LPA as low as 0.2 nM. When the acyl chain at the sn-1 position is altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 28 publications
8
94
4
Order By: Relevance
“…Thus, EDG2 seems to recognize LPAs with both saturated and unsaturated fatty acids like EDG4. It has been previously demonstrated that LPAs with unsaturated fatty acids evoked greater Ca 2Ï© responses of the human epidermoid carcinoma cell line A431 than LPAs with saturated fatty acids (30). In addition, Tokumura et al (31) reported that degree of unsaturation in the acyl moiety of LPA affects proliferation of cultured vascular smooth muscle cells from rat aorta by LPA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, EDG2 seems to recognize LPAs with both saturated and unsaturated fatty acids like EDG4. It has been previously demonstrated that LPAs with unsaturated fatty acids evoked greater Ca 2Ï© responses of the human epidermoid carcinoma cell line A431 than LPAs with saturated fatty acids (30). In addition, Tokumura et al (31) reported that degree of unsaturation in the acyl moiety of LPA affects proliferation of cultured vascular smooth muscle cells from rat aorta by LPA.…”
Section: Discussionmentioning
confidence: 99%
“…Ours is not the first report of activity of phosphonate compounds in assays of LPA receptor activation. In 1991, Proll and Clark reported that an LPA analog with a phosphonate head group inhibits cAMP accumulation (50), but Moolenaar's group later showed that the same compound had little activity with respect to calcium mobilization (12). We have synthesized and tested a similar compound in a GTP␄S binding assay at each Edg/LPA receptor and found that it is an agonist at Edg-2 but has very little activity at Edg-4 or Edg-7.…”
Section: Discussionmentioning
confidence: 99%
“…Hopper et al (56) reported calcium mobilization in response to LPA with an EC 50 of 5 nM in MDA MB-231, and Moolenaar's group (12) has reported an LPA EC 50 of 0.2 nM in A-431 cells, measuring calcium mobilization in a buffer system containing 1 mM calcium. The potency of LPA with respect to inhibition of cAMP accumulation has been measured and reported in two previous papers by us to be 20 nM (13) and 52 nM (14), and these experiments were performed in 1.8 mM calcium.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that LPA induces calcium mobilization [23,24]. As shown in Figure 5, LPAstimulated H # O # release was inhibited when cells were incubated with the intracellular calcium-chelator BAPTA-AM.…”
Section: Role Of Calcium and Pla 2 In Lpa-stimulated H 2 O 2 Releasementioning
confidence: 84%